In vitro GERMINATION AND ACCLIMATIZATION OF EVERLASTING FLOWER - PRUDENTE, DÉBORA DE OLIVEIRA; Nery, Fernanda Carlota; DOS REIS, MICHELE VALQUÍRIA; DE OLIVEIRA PAIVA, PATRÍCIA DUARTE; NERY, MARCELA CARLOTA; AMIN, THAÍS DE OLIVEIRA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
Actinocephalus bongardii (A. St.-Hil.) Sano is a native ornamental specie from Brazil, popularly known as evergreen “showerhead” that presents potential for commercialization. No effective propagation protocol for the species has yet been established. The objective of this work was to establish an in vitro germination protocol and acclimatization of A. bongardii. For the in vitro culture, we evaluated MS and WPM culture media. Three pH levels (4.8, 5.8 and 6.8) and five concentrations of gibberellic acid (GA3) (0.0; 0.2; 0.4; 0.6 and 0.8 mg L-1) in WPM culture media were evaluated. Percentage of germinated seeds, number of leaves and length of the seedlings were evaluated 30 days after inoculation. Seedlings obtained through the in vitro germination were acclimatized with Plantmax® substrate in a greenhouse and the percentage of seedlings survival were evaluated 30 days after acclimatization. The seeds inoculated in WPM showed highest germination percentage (74%) and seedlings with more leaves and longer length. The culture medium pH of 5.8 improved germination and the supplementation of the medium with 0.2 mg L-1 GA3 significantly increased the percentage of seed germination (94%). The acclimatization of the seedlings was only 50% due to the fragility of the tissues.